2014
DOI: 10.4236/health.2014.65059
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics/antibacterial drug use, their marketing and promotion during the post-antibiotic golden age and their role in emergence of bacterial resistance

Abstract: During the post-antibiotic golden age, it has seen a massive antibiotic/antibacterial production and an increase in irrational use of these few existing drugs in the medical and veterinary practice, food industries, tissue cultures, agriculture and commercial ethanol production globally. The irrational drug use has been further exacerbated by the increased marketing and promotion of these drugs by the pharmaceutical companies thus increasing their accessibility in the public and hence their improper use. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 27 publications
0
45
0
5
Order By: Relevance
“…Previous studies have used this technique successfully for taxonomic classification of different bacterial and fungal strains resulted from minor molecular changes . Bacterial susceptibility to antibiotics may be manifested in minor molecular and biochemical changes in the bacterial cells . Recently, Lechowicz et al, reported that FTIR microcopy combined with multivariate analysis methods has a great potential for classification UPEC strains' susceptibility to cephalothin .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used this technique successfully for taxonomic classification of different bacterial and fungal strains resulted from minor molecular changes . Bacterial susceptibility to antibiotics may be manifested in minor molecular and biochemical changes in the bacterial cells . Recently, Lechowicz et al, reported that FTIR microcopy combined with multivariate analysis methods has a great potential for classification UPEC strains' susceptibility to cephalothin .…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that most medical brochures were focusing on treating cardiovascular, gastrointestinal and respiratory diseases, similarly brochures in Nepal focus mainly on cardiovascular drugs, ulcer healing drugs and those for treating respiratory disorders,[ 12 ] additionally it was found in this study that antibiotics were present in 20% of examined brochures, this may be because antibiotics are one of the most commonly dispensed medications in hospital setting,[ 13 ] and since antibiotics considered as prescription only medications so it is reasonable to find that antibiotics are the most commonly promoted drugs to physicians. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, the effective action against these targets inhibits bacteria growth, compromises the cell integrity and, finally, leads to cell death [119,120]. The structural and metabolic differences between bacteria and mammalian cells enables antibiotics to induce selective toxicity against pathogens without harming the host cells [121]. The discovery of penicillin and streptomycin in 1929 and 1943, respectively, foreshadowed the age of antibiotics [117].…”
Section: Antibioticsmentioning
confidence: 99%